The Impact of Financial Report Quality and Performance-Based Budget Implementation on the Accountability Performance of Government Agencies with Accounting Control as a Moderator: Empirical Study of Regional Government Work Units in Bogor City - Wardani, Erlinda Kusuma; Hasibuan, David (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to examine the influence of accounting controls in moderating the relationship between financial reporting quality, the implementation of performance-based budgeting, and performance accountability of government agencies in Local Government Work Units (SKPD) across Bogor City. The research employs a quantitative approach using Structural Equation Modeling (SEM) with PLS software and IBM Statistics SPSS 26.0. The unit of analysis consists of employees with specific criteria within the Regional Apparatus Organizations of Bogor City. The sample consisted of 144 respondents, and data collection was conducted through a questionnaire. The results of the study indicate that financial reporting quality and the implementation of performance-based budgeting have a positive impact on the performance accountability of government agencies in SKPD Bogor City. Furthermore, accounting controls positively moderate the relationship between financial reporting quality and the implementation of performance-based budgeting on the performance accountability of government agencies across SKPD in Bogor City. Keywords: accounting control, quality of financial reports, implementation of performance-based budgeting, accountability for the performance of government agencies